The effects of online exercise prescription on well-being in healthy adults : a thesis completed as part of the requirements for Master of Health Science in Sport and Exercise at Massey University, Albany Campus, Auckland, New Zealand - Bahi, Fadi (Massey University, 2022)
Background: Positive well-being is associated with living a healthy and happy life; increased sedentary behaviour can negatively impact physical and mental health. Therefore, increased engagement in physical activity is necessary to improve quality of life and overall well-being. With the COVID-19 pandemic, it has become apparent that alternative means of health delivery are necessary. Online health delivery can be very effective in reducing limitations associated with in-person care, such as cost of use and travel, waiting time, and lack of availability within rural areas. Despite the benefits, online health delivery is similarly limited in aspects such as the inability of physical inspections and dependence on smart devices and an internet connection. The concept of online exercise delivery remains relatively novel, however, and needs to be further explored. Therefore, the objectives of this study were to determine the effects of online exercise prescription on well-being and understand participant perspectives and opinions on the use of online health delivery. Methods/Design: Seventeen healthy participants were recruited for this study. Nine participants (male = 4, female = 5, mean age = 44 years) were allocated to the online group (INT) and 8 participants (male = 4, female = 4, mean age = 40 years) were allocated to the self-monitoring group (ACON). This study utilised an interpretivist phenomenological approach. All participants attended a 60-minute pre-intervention data collection session where cardiorespiratory (VO₂ₘₐₓ), blood pressure, blood flow and well-being data was collected. Well-being data was derived via a holistic questionnaire completed by participants upon arrival to the laboratory. Cardiorespiratory fitness was assessed via the 6-minute Astrand Rhyming Cycle test and blood flow measures were recorded via a Uscom 1A ultrasound. Participants were also informed which group they were assigned to and provided with an equipment pack containing a Swiss ball, skipping rope, and resistance bands to use throughout the 12-week program. INT participants attended a weekly 20-minute Zoom session where long and short-term goals were set, exercises were prescribed and demonstrated, and feedback was provided. After each weekly session, participants were provided with a link to a YouTube video demonstrating the exercises along with a document containing step-by-step instructions for said exercises. Self-monitoring participants were provided with a 12-week exercise program upfront during the pre-intervention session, and a weekly check-up email was sent to assess progress and determine whether any assistance was needed. The 12-week program consisted of various strength training exercises and progressively increased in resistance throughout the intervention. Online focus group sessions were conducted by a research assistant via Zoom to assess participant perspectives on their respective delivery methods. This data was transcribed and then analysed via phenomenological thematic analysis using Braun and Clark’s process, incorporating codes to identify themes. The initial aim of this study was to determine the effects of online exercise prescription on blood pressure and cardiorespiratory fitness in participants. However, due to a COVID-19 lockdown being announced during the post-intervention data collection period which meant closure of the Massey University laboratory and mandatory social distancing and limited gatherings, we were unable to gather the necessary post-intervention data and hence the study employed a qualitative approach. Hence, the aim of this study was to determine the effects of online exercise prescription on well-being and to understand the varying perspectives of participants on this method. Results: Through phenomenological analyses, the themes identified for the INT group were perceived advantages of online exercise prescription and acceptance of online sessions as a form of health delivery. In the self-monitoring group, the themes consisted of self-monitoring physical activity and using online health delivery in the future. Age and availability of smart devices did not appear to be barriers for online group participants as weekly online Zoom sessions were easily accessed. Overall, online health delivery was well received by participants and most thought it to be effective in improving well-being. Weekly online sessions were considered important in increasing adherence to exercise through accountability, motivation, and feedback. Participants did not want to disappoint the practitioner and therefore effectively completed their prescribed exercises ahead of weekly sessions. In contrast, self-monitoring participants experienced difficulty engaging in physical activity and, as a result, did not perceive any changes in physical well-being, however, interestingly, some did note an improvement in mental well-being. The increased participation in physical activity within the online group led to increased energy levels and physical fitness and strength. Conclusion: Our findings suggest that online health delivery has great potential in the management of health conditions such as hypertension and improving overall well-being in individuals. The online intervention appeared more effective in eliciting a positive physical well-being response compared to the ACON group. It is imperative that further research be undertaken to further expand on the literature and determine whether prescribing physical activity via an online intervention can be implemented in the health sector, and whether this would be effective for those residing in rural locations
Keywords: 420302 Digital health